Implementation of Navigation Target Seeker Mobile Robot Based on Pattern Recognition with Fuzzy Kohonen Network (FKN) Methods - Aditya P. P. Prasetyo; Katjuk Astrowulan; Ali Fatoni (IPTEK Journal of Proceedings Series, 2015)
Navigation is a technique for determining the position and direction of travel in the actual environment. This navigation system can be implemented on a mobile robot to accomplish a specific task, in this paper is used in order to navigate the robot can move toward a specific target while avoiding obstacles exist. One of the control techniques used in mobile robot navigation is based on pattern recognition techniques. With a pattern that has been previously implanted in the “brains” of the robot, the mobile robot can take action in accordance with the movement of the pattern. This paper used method of Fuzzy Kohonen Network (FKN) in order to be able to navigate a mobile robot to recognize patterns in the environment. The target used is a specific point designated position using a camera support (GPS Ad-hoc). Based on test results using this method, the obtained results are satisfactory, precisely to the targets and fast search time targets